2020
DOI: 10.1093/cvr/cvaa128
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying technical confounders in microbiome studies

Abstract: Aims Recent technical developments have allowed the study of the human microbiome to accelerate at an unprecedented pace. Methodological differences may have considerable impact on the results obtained. Thus, we investigated how different storage, isolation, and DNA extraction methods can influence the characterization of the intestinal microbiome, compared to the impact of true biological signals such as intraindividual variability, nutrition, health, and demographics. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 52 publications
0
43
0
Order By: Relevance
“…These aspects are interrelated, since it is thought that both sample collection and preservation methods may have a profound effect on the output of high-throughput sequencing-based technologies used for microbiome determination [ 22 , 48 ]. For example, a cohort study, which quantified technical factors during sample preparation that may affect the characterization of the gut microbiome, showed that DNA extraction methods had the highest impact on the observed microbiome variability, precluding a clear picture of the microbiome signatures of various health and nutrition factors [ 48 ]. Research in food, diet and the gut microbiome would largely benefit from initiatives joining efforts to propose guidelines to standardize stool collection and preservation methods.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These aspects are interrelated, since it is thought that both sample collection and preservation methods may have a profound effect on the output of high-throughput sequencing-based technologies used for microbiome determination [ 22 , 48 ]. For example, a cohort study, which quantified technical factors during sample preparation that may affect the characterization of the gut microbiome, showed that DNA extraction methods had the highest impact on the observed microbiome variability, precluding a clear picture of the microbiome signatures of various health and nutrition factors [ 48 ]. Research in food, diet and the gut microbiome would largely benefit from initiatives joining efforts to propose guidelines to standardize stool collection and preservation methods.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these limitations, our collection of studies enables comparisons since multiple studies amplified the same region, e.g., V4 ( n = 3 studies) and V3–V4 ( n = 11), and five have conducted both marker gene and shotgun metagenome sequencing. This underlines the importance of standardizing, providing detailed descriptions of methods, and determining technical factors that are critical for the comparability of studies [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All biomaterials, in particular, stool samples, are collected with the highest scientific standards to allow for high-quality microbiome analyses [23].…”
Section: Discussionmentioning
confidence: 99%
“…One major challenge is that several covariates are known to introduce unwanted variation and systematically bias the relative abundances of taxonomic units in microbiome samples [10][11][12][13][14][15][16] . These covariates include host diet and sex [17][18][19] , sample storage 20 , cell lysis protocol 10,21 , DNA preservation and storage protocol 22 , preparation kit 23 , extraction method 24,25 , and primer choice 21 . This variation can substantially reduce the ability to predict host phenotypes from microbiome data.…”
Section: Introductionmentioning
confidence: 99%